An analytic study of the problem of improving the teaching of biological sciences in the University of the East - Magdamo, Lourdes M. (Gruela) 1927- (s.n.], 1969)
The study determined and analyzed the problems of implementing modern biology teaching in the University of the East. The objective of the study, which is descriptive in nature, is to improve the teaching of the biological sciences in the University of the East.